Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

A Value-Centered Approach for Unique and Novel Software Applications - Senft, Björn; Rittmeier, Florian; Fischer, Holger Gerhard; Oberthür, Simon (Design, User Experience, and Usability. Practice and Case Studies)

Exploiting Counterfactuals for Scalable Stochastic Optimization - Kuhlemann, Stefan; Sellmann, Meinolf; Tierney, Kevin (Lecture Notes in Computer Science)

Feature Selection for Analogy-Based Learning to Rank - Ahmadi Fahandar, Mohsen; Hüllermeier, Eyke (Discovery Science)

Analogy-Based Preference Learning with Kernels - Ahmadi Fahandar, Mohsen; Hüllermeier, Eyke (KI 2019: Advances in Artificial Intelligence)

Epistemic Uncertainty Sampling - Nguyen, Vu-Linh; Destercke, Sébastien; Hüllermeier, Eyke (Discovery Science)

How Good Is Good Enough? Establishing Quality Thresholds for the Automatic Text Analysis of Retro-Digitized Comics - Hartel, Rita; Dunst, Alexander (International Conference on Multimedia Modeling, MMM)

CoVeriTest: Cooperative Verifier-Based Testing - Beyer, Dirk; Jakobs, Marie-Christine (Fundamental Approaches to Software Engineering)

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Parameterised Complexity of Abduction in Schaefer’s Framework - Mahmood, Yasir; Meier, Arne; Schmidt, Johannes (Logical Foundations of Computer Science)

Practical, Anonymous, and Publicly Linkable Universally-Composable Reputation Systems - Blömer, Johannes; Eidens, Fabian; Juhnke, Jakob (Topics in Cryptology - CT-RSA 2018 - The Cryptographers' Track at the RSA Conference 2018, Proceedings)

An Optimal Algorithm for Online Prize-Collecting Node-Weighted Steiner Forest - Markarian, Christine (International Workshop on Combinatorial Algorithms (IWOCA))
We study the Online Prize-collecting Node-weighted Steiner Forest problem (OPC-NWSF) in which we are given an undirected graph \(G=(V, E)\) with \(|V| = n\) and node-weight function \(w: V → \mathcal {R}^+\). A sequence of k pairs of nodes of G, each associated with a penalty, arrives online. OPC-NWSF asks to construct a subgraph H such that each pair \(\{s, t\}\) is either connected (there is a path between s and t in H) or its associated penalty is paid. The goal is to minimize the weight of H and the total penalties paid. The current best result for OPC-NWSF is a randomized \(\mathcal {O}(\log ^4 n)\)-competitive algorithm due to Hajiaghayi et al. (ICALP 2014). We improve this by proposing a randomized \(\mathcal {O}(\log n \log k)\)-competitive algorithm for OPC-NWSF, which is optimal up to constant factor since OPC-NWSF has a randomized lower bound of \(\varOmega (\log ^2 n)\) due to Korman [11]. Moreover, our result also implies an improvement for two special cases of OPC-NWSF, the Online Prize-collecting Node-weighted Steiner Tree problem (OPC-NWST) and the Online Node-weighted Steiner Forest problem (ONWSF). In OPC-NWST, there is a distinguished node which is one of the nodes in each pair. In ONWSF, all penalties are set to infinity. The currently best known results for OPC-NWST and ONWSF are a randomized \(\mathcal {O}(\log ^3 n)\)-competitive algorithm due to Hajiaghayi et al. (ICALP 2014) and a randomized \(\mathcal {O}(\log n \log ^2 k)\)-competitive algorithm due to Hajiaghayi et al. (FOCS 2013), respectively.

Ampehre: An Open Source Measurement Framework for Heterogeneous Compute Nodes - Lösch, Achim; Wiens, Alex; Platzner, Marco (Proceedings of the International Conference on Architecture of Computing Systems (ARCS))
Profiling applications on a heterogeneous compute node is challenging since the way to retrieve data from the resources and interpret them varies between resource types and manufacturers. This holds especially true for measuring the energy consumption. In this paper we present Ampehre, a novel open source measurement framework that allows developers to gather comparable measurements from heterogeneous compute nodes, e.g., nodes comprising CPU, GPU, and FPGA. We explain the architecture of Ampehre and detail the measurement process on the example of energy measurements on CPU and GPU. To characterize the probing effect, we quantitatively analyze the trade-off between the accuracy of measurements and the CPU load imposed by Ampehre. Based on this analysis, we are able to specify reasonable combinations of sampling periods for the different resource types of a compute node.

An FPGA/HMC-Based Accelerator for Resolution Proof Checking - Hansmeier, Tim; Platzner, Marco; Andrews, David (ARC 2018: Applied Reconfigurable Computing. Architectures, Tools, and Applications)
Modern Boolean satisfiability solvers can emit proofs of unsatisfiability. There is substantial interest in being able to verify such proofs and also in using them for further computations. In this paper, we present an FPGA accelerator for checking resolution proofs, a popular proof format. Our accelerator exploits parallelism at the low level by implementing the basic resolution step in hardware, and at the high level by instantiating a number of parallel modules for proof checking. Since proof checking involves highly irregular memory accesses, we employ Hybrid Memory Cube technology for accelerator memory. The results show that while the accelerator is scalable and achieves speedups for all benchmark proofs, performance improvements are currently limited by the overhead of transitioning the proof into the accelerator memory.

FastLane Is Opaque – a Case Study in Mechanized Proofs of Opacity - Schellhorn, Gerhard; Wedel, Monika; Travkin, Oleg; König, Jürgen; Wehrheim, Heike (Software Engineering and Formal Methods)

Information Flow Certificates - Töws, Manuel; Wehrheim, Heike (Theoretical Aspects of Computing – ICTAC 2018)
Information flow analysis investigates the flow of data in applications, checking in particular for flows from private sources to public sinks. Flow- and path-sensitive analyses are, however, often too costly to be performed every time a security-critical application is run. In this paper, we propose a variant of proof carrying code for information flow security. To this end, we develop information flow (IF) certificates which get attached to programs as well as a method for IF certificate validation. We prove soundness of our technique, i.e., show it to be tamper-free. The technique is implemented within the program analysis tool CPAchecker. Our experiments confirm that the use of certificates pays off for costly analysis runs.

Assist Users to Straightaway Suggest and Describe Experienced Problems - Senft, Björn; Fischer, Holger Gerhard; Oberthür, Simon; Patkar, Nitish (Design, User Experience, and Usability: Theory and Practice)

A Canvas Method to Foster Interdisciplinary Discussions on Digital Assistance Systems - Fischer, Holger Gerhard; Senft, Björn; Rittmeier, Florian; Sauer, Stefan (Design, User Experience, and Usability: Theory and Practice. Proceedings of the 20th International Conference on Human-Computer Interaktion (HCI International 2018))

Preference-Based Reinforcement Learning Using Dyad Ranking - Schäfer, Dirk; Hüllermeier, Eyke (Discovery Science)

A Dynamic Distributed Data Structure for Top-k and k-Select Queries - Feldkord, Björn; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Progress in Pattern Recognition, Image Analysis, Computer Vision, and Applications)

Scheduling Access to Shared Space in Multi-robot Systems - Khaluf, Yara; Markarian, Christine; Simoens, Pieter; Reina, Andreagiovanni (International Conference on Practical Applications of Agents and Multi-Agent Systems (PAAMS 2017))
Through this study, we introduce the idea of applying scheduling techniques to allocate spatial resources that are shared among multiple robots moving in a static environment and having temporal constraints on the arrival time to destinations. To illustrate this idea, we present an exemplified algorithm that plans and assigns a motion path to each robot. The considered problem is particularly challenging because: (i) the robots share the same environment and thus the planner must take into account overlapping paths which cannot happen at the same time; (ii) there are time deadlines thus the planner must deal with temporal constraints; (iii) new requests arrive without a priori knowledge thus the planner must be able to add new paths online and adjust old plans; (iv) the robot motion is subject to noise thus the planner must be reactive to adapt to online changes. We showcase the functioning of the proposed algorithm through a set of agent-based simulations.

Subtleties in Security Definitions for Predicate Encryption with Public Index - Blömer, Johannes; Liske, Gennadij (Proceedings of the International Conference of Mathematical Aspects of Computer and Information Sciences (MACIS))

Attribute-Based Encryption as a Service for Access Control in Large-Scale Organizations - Blömer, Johannes; Günther, Peter; Krummel, Volker; Löken, Nils (Foundations and Practice of Security)

Complexity of Single-Swap Heuristics for Metric Facility Location and Related Problems - Brauer, Sascha (Lecture Notes in Computer Science)
Metric facility location and K-means are well-known problems of combinatorial optimization. Both admit a fairly simple heuristic called single-swap, which adds, drops or swaps open facilities until it reaches a local optimum. For both problems, it is known that this algorithm produces a solution that is at most a constant factor worse than the respective global optimum. In this paper, we show that single-swap applied to the weighted metric uncapacitated facility location and weighted discrete K-means problem is tightly PLS-complete and hence has exponential worst-case running time.

Policy Dependent and Independent Information Flow Analyses - Töws, Manuel; Wehrheim, Heike (Formal Methods and Software Engineering - 19th International Conference on Formal Engineering Methods (ICFEM 2017))
Information Flow Analysis (IFA) aims at detecting illegal flows of information between program entities. “Legality” is therein specified in terms of various security policies. For the analysis, this opens up two possibilities: building generic, policy independent and building specific, policy dependent IFAs. While the former needs to track all dependencies between program entities, the latter allows for a reduced and thus more efficient analysis. In this paper, we start out by formally defining a policy independent information flow analysis. Next, we show how to specialize this IFA via policy specific variable tracking, and prove soundness of the specialization. We furthermore investigate refinement relationships between policies, allowing an IFA for one policy to be employed for its refinements. As policy refinement depends on concrete program entities, we additionally propose a precomputation of policy refinement conditions, enabling an efficient refinement check for concrete programs.

A Human-Centered Perspective on Software Quality: Acceptance Criteria for Work 4.0 - Fischer, Holger Gerhard; Engler, Michael; Sauer, Stefan (Design, User Experience, and Usability: Theory, Methodology, and Management)

Monitoring of Domain-Related Problems in Distributed Data Streams - Bemmann, Pascal; Biermeier, Felix; Bürmann, Jan; Kemper, Arne; Knollmann, Till; Knorr, Steffen; Kothe, Nils; Mäcker, Alexander; Malatyali, Manuel; Meyer auf der Heide, Friedhelm; Riechers, Sören; Schaefer, Johannes Sebastian; et al. (Structural Information and Communication Complexity)

Simulating Storage Policies for an Automated Grid-Based Warehouse System - Beckschäfer, Michaela; Malberg, Simon; Tierney, Kevin; Weskamp, Christoph (Lecture Notes in Computer Science)

Reducing the Verbosity of Imperative Model Refinements by Using General-Purpose Language Facilities - Gerking, Christopher; Schubert, David; Budde, Ingo (Theory and Practice of Model Transformation)

Population Coding: A New Design Paradigm for Embodied Distributed Systems - Hamann, Heiko; Valentini, Gabriele; Dorigo, Marco (10th Int. Conf. on Swarm Intelligence, ANTS 2016)

Collective Perception of Environmental Features in a Robot Swarm - Valentini, Gabriele; Brambilla, Davide; Hamann, Heiko; Dorigo, Marco (10th Int. Conf. on Swarm Intelligence, ANTS 2016)

Implementing Cryptographic Pairings on Accumulator Based Smart Card Architectures - Günther, Peter; Krummel, Volker (Mathematical Aspects of Computer and Information Sciences)

Theoretical Analysis of the k-Means Algorithm – A Survey - Blömer, Johannes; Lammersen, Christiane; Schmidt, Melanie; Sohler, Christian (Algorithm Engineering)

Adaptive Seeding for Gaussian Mixture Models - Blömer, Johannes; Bujna, Kathrin (Advances in Knowledge Discovery and Data Mining)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Cross-Device Integration of Android Apps - Wolters, Dennis; Kirchhoff, Jonas; Gerth, Christian; Engels, Gregor (Service-Oriented Computing)
Integrating apps on mobile devices into applications running on other devices is usually difficult. For instance, using a messenger on a smartphone to share a text written on a desktop computer often ends up in a cumbersome solution to transfer the text, because many applications are not designed for such scenarios. In this paper, we present an approach enabling the integration of apps running on Android devices into applications running on other devices and even other platforms. This is achieved by specifying adapters for Android apps, which map their services to a platform-independent service interface. For this purpose, we have developed a domain-specific language to ease the specification of such mappings. Our approach is applicable without the need to modify the existing Android apps providing the service. We analyzed its feasibility by implementing our approach and by specifying mappings for several popular Android apps, e.g., phone book, camera, and file explorer.
Keywords: Cross-Device; Integration; Android; Adapter; DSL

Human-Centered Software Engineering as a Chance to Ensure Software Quality Within the Digitization of Human Workflows - Fischer, Holger Gerhard; Senft, Björn (Human-Centered and Error-Resilient Systems Development)

Adaptive Seeding for Gaussian Mixture Models - Blömer, Johannes; Bujna, Kathrin (Advances in Knowledge Discovery and Data Mining)

Tightly-Secure Signatures from Chameleon Hash Functions - Blazy, Olivier; Kakvi, Saqib; Kiltz, Eike; Pan, Jiaxin (Lecture Notes in Computer Science)

AdIDoS – Adaptive and Intelligent Fully-Automatic Detection of Denial-of-Service Weaknesses in Web Services - Altmeier, Christian; Mainka, Christian; Somorovsky, Juraj; Schwenk, Jörg (Data Privacy Management, and Security Assurance - 10th International Workshop, DPM 2015, and 4th International Workshop, QASA 2015)

Practical Invalid Curve Attacks on TLS-ECDH - Jager, Tibor; Schwenk, Jörg; Somorovsky, Juraj (Computer Security -- ESORICS 2015)

ECST – Extended Context-Free Straight-Line Tree Grammars - Böttcher, Stefan; Hartel, Rita; Jacobs, Thomas; Jeromin, Markus (Data Science - 30th British International Conference on Databases, BICOD 2015)

Understanding the Patient 2.0 - Geierhos, Michaela; Bäumer, Frederik S.; Schulze, Sabine; Klotz, Caterina (Modeling and Using Context)

Understanding the Patient 2.0 - Geierhos, Michaela; Bäumer, Frederik S.; Schulze, Sabine; Klotz, Caterina (Modeling and Using Context)

Swarm in a Fly Bottle: Feedback-Based Analysis of Self-organizing Temporary Lock-ins - Hamann, Heiko; Valentini, Gabriele (Ninth Int. Conf. on Swarm Intelligence (ANTS 2014))

Generating EAST-ADL Event Chains from Scenario-Based Requirements Specifications - Koch, Thorsten; Holtmann, Jörg; DeAntoni, Julien (Software Architecture)
Real-time software-intensive embedded systems complexity, as in the automotive domain, requires rigorous Requirements Engineering (RE) approaches. Scenario-based RE formalisms like Modal Sequence Diagrams (MSDs) enable an intuitive specication and the simulative validation of functional requirements. However, the dependencies between events occurring in different MSD scenarios are implicit so that it is difficult to find causes of requirements defects, if any. The automotive architecture description language EAST-ADL addresses this problem by relying on event chains, which make dependencies between events explicit. However, EAST-ADL event chains have a low abstraction level, and their relationship to functional requirements has seldom been investigated. Based on the EAST-ADL functional architecture, we propose to use its central notion of event to conciliate both approaches. We conceived an automatic transformation from the high abstraction level requirements specified in MSDs to the low abstraction level event chains.

Use Your Best Device! Enabling Device Changes at Runtime - Bokermann, Dennis; Gerth, Christian; Engels, Gregor (12th International Conference on Business Process Management (BPM 2014))

Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics, ALGOSENSORS 2013

Efficient XML Keyword Search Based on DAG-Compression - Böttcher, Stefan; Hartel, Rita; Rabe, Jonathan (Database and Expert Systems Applications - 25th International Conference, DEXA 2014)

Fast Collisionless Pattern Formation by Anonymous, Position-Aware Robots - Lukovszki, Tamás; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)